Chitosan Based MicroRNA Nanocarriers - Hussein H. Genedy; Thierry Delair; Alexandra Montembault (MDPI AG, 2022)
Vectorization of microRNAs has shown to be a smart approach for their potential delivery to treat many diseases (i.e., cancer, osteopathy, vascular, and infectious diseases). However, there are barriers to genetic in vivo delivery regarding stability, targeting, specificity, and internalization. Polymeric nanoparticles can be very promising candidates to overcome these challenges. One of the most suitable polymers for this purpose is chitosan. Chitosan (CS), a biodegradable biocompatible natural polysaccharide, has always been of interest for drug and gene delivery. Being cationic, chitosan can easily form particles with anionic polymers to encapsulate microRNA or even complex readily forming polyplexes. However, fine tuning of chitosan characteristics is necessary for a successful formulation. In this review, we cover all chitosan miRNA formulations investigated in the last 10 years, to the best of our knowledge, so that we can distinguish their differences in terms of materials, formulation processes, and intended applications. The factors that make some optimized systems superior to their predecessors are also discussed to reach the highest potential of chitosan microRNA nanocarriers.